Development of a dehydrated dressing-type emulsion with instant powder characteristics. (April 2019) - Plati, Fotini; Matsakidou, Anthia; Kiosseoglou, Vassilios; Paraskevopoulou, Adamantini
Graphical abstract: Highlights: Instant dressing-type emulsion powders were developed by two dehydration methods. Oven-drying resulted in irregular-shaped particles of high free oil content. Nano spray drying led to spherical, small particles of low free oil content. Spray-dried powders exhibited satisfactory reconstitution ability. All powders were characterised by high cohesiveness and poor flowability. Abstract: In this work the development of a dressing-type emulsion powder with instant characteristics was attempted. Two dehydration methods (oven-drying and nano spray drying) were evaluated using maltodextrin in admixture with carboxymethyl cellulose or gum Arabic as coating materials. Droplet size distribution of the initial emulsions was first considered, while the resulting powders were analysed for moisture, total and free oil content, oil encapsulation efficiency, morphological characteristics, physical and flow properties and reconstitution behaviour. The results showed that particles of irregular shape, micron size, high free oil content and low encapsulation efficiency were obtained through oven-drying, while nano spray drying led to spherical, of smaller average diameter powder particles along with lower "free" oil content and higher encapsulation efficiency. Regarding their handling properties, all powders were very cohesive with poor flowability. Dehydration method significantly affected both bulk and reconstitution properties with the spray-dried powders exhibiting lower bulk and tapped density, higher dispersibility and satisfactory wettability, all related to their instantaneous character. This powdered dressing-type emulsion can be used as it is by sprinkling directly on vegetable salads and other food or by dispersing in water.